In vivo drug tracking with 19F MRI at therapeutic dose. Issue 31 (29th March 2018) - Bo, Shaowei; Yuan, Yaping; Chen, Yongping; Yang, Zhigang; Chen, Shizhen; Zhou, Xin; Jiang, Zhong-Xing
Abstract : A fluorinated amphiphile facilitates the sensitive 19 F MRI tracking of doxorubicin at its therapeutic dose through the construction of fluorinated liposomal drug delivery systems. Abstract : Tracking drugs with 19 F MRI would be beneficial for developing theranostics and optimizing drug therapy. To this end, a fluorinated dendritic amphiphile with high 19 F MRI sensitivity and biocompatibility has been developed for 19 F MRI tracking of doxorubicin (DOX)-loaded liposomes in mice, which may provide an effective platform to in vivo trace various drugs with 19 F MRI.